1974
DOI: 10.1002/andp.19744860307
|View full text |Cite
|
Sign up to set email alerts
|

Zur Anregung und Emission im N2‐Impulsgaslaser

Abstract: A theoretical treatment of pulsed nitrogen laser operation is presented. The propertien of laser pulses were investigated as functions of various parameters (electric circuit parameters, laser length, gas pressure). Based on this model some conditions are obtained which are necessary for effective laser pulse emission, and the known nitrogen laser devices are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
1993
1993

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…When a high laser power level in the laser medium is reached, the saturation approximation ( N , = NB) becomes valid because the inversion density N , -NB is rapidly decreased by the stimulated emission process. By assuming N, = NB, Guendel and Ross (1974) have calculated that P, can be expressed by where M , defined by Guendel and Ross (1974), is about 1.…”
Section: Measurements On Non-lte Discharges and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a high laser power level in the laser medium is reached, the saturation approximation ( N , = NB) becomes valid because the inversion density N , -NB is rapidly decreased by the stimulated emission process. By assuming N, = NB, Guendel and Ross (1974) have calculated that P, can be expressed by where M , defined by Guendel and Ross (1974), is about 1.…”
Section: Measurements On Non-lte Discharges and Discussionmentioning
confidence: 99%
“…These discharges have been widely used, especially for excitation of numerous laser transitions in gases. Theories of pulsed gas lasers, for instance the models developed by Gerry (1965), Ali et aZ(1967) and Guendel and Ross (1974) refer to discharges in uniform electric fields. Bohmeyer et aZ (1977) have shown that the results obtained from measurements on these discharges could be described with a model developed by Guendel (1973).…”
Section: Introductionmentioning
confidence: 99%